A novel strong AIE bi-component hydrogel as a multi-functional supramolecular fluorescent material. (December 2019) - Yang, Hai-Long; Zhang, Qin-Peng; Zhang, You-Ming; Gong, Guan-Fei; Chen, Yan-Yan; Qi-Zhou,; Yao, Hong; Wei, Tai-Bao; Lin, Qi
Abstract: Multi-functional supramolecular fluorescent materials are an intriguing concern for materials science. Herein, an easily prepared bi-component hydrogel with strong aggregation-induced emission (AIE) (MQ -G ) was successfully constructed by the gelators naphthalimide derivative (M ) and tri-(pyridine-4-yl)-functionalized trimesic amide (Q ) in DMSO-H2 O (6 : 4, v/v) via π−π, hydrogen bond and π−electron donor-acceptor interactions. The obtained bi-component hydrogelMQ -G has an excellent self-healing property. Interestingly, theMQ -G exhibits strong orange AIE, the fluorescence quantum yield of theMQ -G was measured as 0.578. Moreover, theMQ -G could successively sense Fe 3+ and H2 PO4 − in water through a fluorescent "ON-OFF-ON" pathway, which suggests theMQ -G could serve as an "ON-OFF-ON" fluorescent material and efficient logic gate. Meanwhile, the xerogel ofMQ -G is capable of removing Fe 3+ at an adsorption rate of 99.74% in diluted aqueous solution. Moreover, the thin films based on theMQ -G andMQ -G + Fe 3+ were also prepared, which could not only act as supramolecular fluorescent material but a simple and efficient tool for detection Fe 3+ and H2 PO4 −, respectively. Graphical abstract: Image 1 Highlights: A novel multi-functional AIE bi-component hydrogel (MQ -G ) was constructed. TheMQ -G shows self-healing property and high fluorescent quantum yield (Φ = 0.578). TheMQ -G could successively sense Fe 3+ and H2 PO4 − in water. Fe 3+ could be removed byMQ -G from water (removal rate is 99.72%). TheMQ -G could serve as fluorescent display material, logic gate and ions test tool.